Proton exchange membrane compounded on basis of large-area single-layer nano-porous graphene Nafion and method for preparing proton exchange membrane

By introducing large-area single-layer nanoporous graphene into the proton exchange membrane and performing plasma pore formation, the problem of insufficient methanol selectivity in the existing proton exchange membrane is solved, and the synchronous improvement of high methanol selectivity and high proton conductivity is achieved. , improves the performance of direct methanol fuel cells.

CN119400919AActive Publication Date: 2025-02-07XI AN JIAOTONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411511401.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing proton exchange membranes are insufficient methanol selectivity in direct methanol fuel cells, resulting in fuel loss and degradation of battery performance.

Method used

Large-area single-layer nanoporous graphene is used to recombine with Nafion, and fine pores are made on the graphene surface through plasma pore making technology to improve methanol selectivity and proton conduction performance.

Benefits of technology

The synchronous improvement of high methanol selectivity and high proton conductivity is achieved, the problem of trade-offs of proton exchange membrane selectivity and proton conductivity is solved, and the open circuit voltage and power density of direct methanol fuel cells are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400919A_ABST
    Figure CN119400919A_ABST
Patent Text Reader

Abstract

The invention discloses a composite proton exchange membrane based on large-area single-layer nano-porous graphene Nafion and a preparation method of the composite proton exchange membrane. The preparation method comprises the following steps: firstly, performing plasma etching to obtain a graphene / copper foil sample; spin-coating Nafion latex on the graphene surface of the graphene / copper foil sample; the spin-coated graphene / copper foil sample is dried and cured, a Nafion film is hot-pressed on the spin-coated surface of the graphene sample, and a Nafion / graphene / copper foil sample is obtained; the method comprises the following steps: etching a Nafion / graphene / copper foil sample in an etching solution, then washing the sample, and completing etching, cleaning and airing of the residual copper foil; the Nafion latex is continuously spin-coated; the spin-coated Nafion / graphene sample is dried and cured, and then the spin-coated Nafion / graphene sample and a Nafion thin film are subjected to hot-pressing compounding; and soaking the Nafion / graphene / Nafion sample in an acid solution, and airing to obtain the proton exchange membrane based on the large-area single-layer nano-porous graphene Nafion composite. According to the invention, the bottleneck of performance improvement caused by insufficient selectivity of the proton exchange membrane and low proton transmission efficiency of the intrinsic graphene is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of direct methanol fuel cells, and specifically relates to a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite and a preparation method thereof. Background Art

[0002] Direct methanol fuel cell (DMFC) has a wide range of application potentials in portable electronic devices, backup power supplies and small vehicles due to its simple structure, easy fuel supply, high energy density and renewable energy. In the DMFC system, the proton exchange membrane (PEM) is a core component that conducts protons and prevents the fuel, namely methanol molecules, from passing through. Perfluorosulfonic acid (PFSA) membrane, commonly known as Nafion, has been the main commercial PEM material. Nafion is composed of a hydrophobic polytetrafluoroethylene (PTFE) backbone and a hydrophilic sulfonic acid (-SO3H) side chain, providing excellent proton conductivity, mechanical strength, chemical stability and durability. However, Nafion has poor selectivity between protons and other ions or small molecules, which hinders the further improvement of electrochemical energy systems. In fuel cells, the resulting permeation problem can lead to fuel loss, reduce cathode voltage and affect cell performance. In direct methanol fuel cells (DMFCs), due to the high methanol permeability of currently commercial proton exchange membranes, about 40% of the methanol may penetrate the membrane and be lost. To mitigate methanol permeation, DMFCs usually use thicker Nafion membranes, which can lead to reduced fuel cell performance. Given Nafion's excellent proton conductivity, a lot of research has been devoted to retaining the Nafion system and modifying it to meet application requirements. Researchers have tried to reduce permeation by composite and hybridizing Nafion with low methanol-compatible polymers and inorganic nanoparticles, surface modification, or multilayer systems. Nafion and nanomaterial doped membranes usually significantly improve their physical and electrical properties by adding a small amount of nanoparticles or nanofillers. However, the modified Nafion membrane usually leads to a slight decrease in proton conductivity, and the added nanoparticles increase the tortuosity of proton transport, which may reduce the overall performance.

[0003] Different solutions have been proposed in response to the growing interest in large-area 2D materials. In 2016, Zhao Tianshou et al. sandwiched a large-area monolayer graphene between two Nafion membranes and applied it in DMFCs. They reported an improvement in open circuit voltage (OCV) performance, while the decrease in power density was not significant, highlighting the potential of graphene in reducing methanol permeation. The introduction of large-area monolayer 2D materials avoids the problem of tortuosity in proton conduction pathways and may provide controllable selective nanopores adapted to specific application needs. Bukola et al. demonstrated excellent proton conduction through graphene intrinsic hexagonal pores and through water molecules in the liquid phase via Grothuss and carrier mechanisms. Meanwhile, the excellent selectivity of monolayer graphene has been studied in the fields of organic separation, gas separation, and water desalination. Therefore, large-area 2D materials such as graphene bring new opportunities for the development of new proton exchange membranes.

[0004] Although the introduction of graphene has alleviated the methanol permeation problem in DMFC applications, there is still much room for improvement in ensuring proton conductivity and improving fuel cell performance. By creating pores on a large area of ​​graphene surface, the proton penetration resistance can be reduced while maintaining precise selectivity, thereby improving the performance of the overall proton exchange membrane. Ion bombardment is a method of creating atomic-precision nanopores by carefully controlling parameters, but its application scale is limited by equipment. In contrast, plasma can achieve large-area atomic-level pore creation. Mahurin et al. used oxygen plasma etching technology to adjust the pore size of single-layer graphene, achieving efficient ion selection and rapid water transport in seawater desalination applications. Similarly, Karnik et al. used oxygen plasma etching technology to form selective pores ≤1 nm in CVD graphene, improving K + Ion selectivity for small molecules and proteins. To overcome the mutual limitation between pore size and pore density in plasma pore formation, Wang et al. proposed a method to control the pore density using high-energy argon plasma and then control the pore size using low-energy oxygen plasma. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a proton exchange membrane based on a large-area single-layer nanoporous graphene and Nafion composite and a preparation method thereof in view of the deficiencies in the above-mentioned prior art, so as to solve the technical problem of insufficient methanol selectivity of the proton exchange membrane: a large-area single-layer graphene is introduced on the basis of a commercial Nafion membrane; and combined with plasma pore-making technology, fine pores are made on the graphene surface to achieve high methanol selectivity and high proton conductivity at the same time.

[0006] The present invention adopts the following technical solutions: A method for preparing a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite comprises the following steps: S1, performing plasma etching on the graphene sample to obtain a porous graphene / copper foil sample; S2, spin coating a layer of Nafion latex on the graphene surface of the porous graphene / copper foil sample prepared in step S1, and repeating the process multiple times; S3, drying and curing the porous graphene / copper foil sample after spin coating in step S2 on a hot stage, hot pressing a Nafion film on the spin-coated side of the graphene sample to obtain a Nafion / porous graphene / copper foil sample; S4, etching the Nafion / porous graphene / copper foil sample after hot pressing in step S3 in an etching solution to remove the material attached to the back of the copper foil, then rinsing the back of the Nafion film, placing it in a clean etching solution to etch the remaining copper foil, and washing and drying it after the etching is completed to obtain a Nafion / porous graphene sample; S5, continuing to spin-coat a layer of Nafion latex on the graphene surface of the Nafion / porous graphene sample dried in step S4; S6, drying and curing the Nafion / porous graphene sample after spin coating in step S5 on a hot stage, and then hot-pressing and compounding with another Nafion film to obtain a Nafion / porous graphene / Nafion sample; S7, soaking the Nafion / porous graphene / Nafion sample prepared in step S6 in an acid solution and then drying it to obtain a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite.

[0007] Preferably, in step S1, the graphene on the copper substrate obtained by chemical vapor deposition growth is flattened by using a glass plate to flatten the copper foil with the graphene surface facing up, so that the sample is attached to the glass plate; the glass plate is placed in a cavity of a plasma cleaning agent, and vacuumed for 5 to 30 minutes, and the argon gas pressure in the cavity is adjusted to 1.5 to 1.7 mbar and then balanced for 5 to 30 minutes, the plasma generation power is set to 15 to 25 W, and the argon plasma etching time is 5 to 10 seconds; after the cavity is broken by vacuum, a Faraday copper mesh is placed on the graphene sample, and after vacuuming for 5 to 30 minutes, the oxygen gas pressure in the cavity is adjusted to 0.25 to 0.4 mbar and then balanced for 5 to 30 minutes, and the plasma generation power is set to 5 to 10 W.

[0008] Preferably, in step S2, spin coating a layer of Nafion latex is specifically: Spin coat at 400-500 rpm for 10-30 seconds, and then at 500-1500 rpm for 30-60 seconds to complete a layer of Nafion latex.

[0009] Preferably, in step S3, the drying and curing temperature is 115-140° C. and the time is 10-30 min.

[0010] Preferably, the thickness of the Nafion film is 12-183 μm, the pressure used for hot pressing is 2.5-4.0 MPa, the hot pressing time is 2-10 min, and the hot pressing temperature is 125-140° C.

[0011] Preferably, in step S4, the etching time is 5 to 10 minutes; the back of the copper foil is rinsed with deionized water, and then the remaining copper foil is etched with a 0.1 to 0.5 M FeCl3 solution; after etching for 1 to 3 hours, the transparent N212 / graphene film is washed in deionized water for 5 to 30 minutes, washed with a 5% to 15% HCl solution for 5 to 30 minutes, and finally washed again with deionized water for 5 to 30 minutes.

[0012] Preferably, in step S5, continuing to spin-coat a layer of Nafion latex is specifically as follows: Spin at 400-500 rpm for 10-30 s, then at 500-1500 rpm for 30-60 s.

[0013] Preferably, in step S6, the drying and curing temperature is 115-140°C, the time is 10-30 min, and then a Nafion film with a thickness of 12-183 μm is selected, and the Nafion film with the spin-coated surface of the Nafion / graphene / copper foil sample facing upward is hot-pressed, the hot-pressing pressure is 2.5-4.0 MPa, the hot-pressing time is 2-10 min, and the hot-pressing temperature is 125-140°C.

[0014] Preferably, in step S7, the acid solution is a 5% to 15% HCl solution, and the soaking time is 10 to 40 hours.

[0015] Another technical solution of the present invention is to achieve an open circuit voltage of more than 0.5V and a conductivity of 130 mW cm-2 under the test conditions of 60-90°C based on a large-area single-layer nanoporous graphene Nafion composite proton exchange membrane. -2 Maximum power density above .

[0016] Compared with the prior art, the present invention has at least the following beneficial effects: A method for preparing a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite, utilizing the high selectivity and ultra-short transmission path characteristics of large-area single-layer graphene, performing surface pore creation on its basis, while ensuring its high selectivity, while improving its proton conductivity, and precisely compounding it with a commercial Nafion membrane, to invent a new proton exchange membrane that can simultaneously provide high proton conductivity and high methanol selectivity, effectively solving the performance improvement bottleneck of proton exchange membranes due to insufficient selectivity and the trade-off limitations between selectivity and proton conductivity.

[0017] Furthermore, plasma pore creation is performed on large-area single-layer graphene, which can finely control the pore size in the graphene. On the basis of ensuring methanol selectivity, the proton conductivity capacity is further improved, thus avoiding the decrease in membrane proton conductivity caused by the introduction of graphene.

[0018] Furthermore, spin coating of Nafion emulsion on the porous graphene surface can enhance its interfacial affinity with the Nafion film during subsequent hot pressing, effectively reduce the interfacial gap between Nafion and graphene, improve the stability of the composite membrane, and shorten the transmission path of protons at the interface.

[0019] Furthermore, after the surface of the porous graphene is spin-coated, heating is performed to promote surface curing, which can help to stably composite the spin-coated layer and the porous graphene, and provide a surface protection layer for the porous graphene to prevent subsequent hot pressing from damaging the porous graphene due to local stress.

[0020] Furthermore, by selecting a Nafion membrane with a thickness of 12 to 183 μm, sufficient mechanical support can be provided for porous graphene, and the thickness of Nafion will not have a negative impact on the performance of the overall membrane. There are a variety of commercial specifications of Nafion membranes within this thickness range. The temperature set for hot pressing is close to the glass transition temperature of the Nafion membrane, which is conducive to achieving a good fit between the Nafion membrane and the Nafion latex layer; the selection of hot pressing time and pressure takes into account providing appropriate pressure to make the Nafion interface fit well, while preventing damage to porous graphene caused by excessive pressure or too long pressurization time.

[0021] Furthermore, the back side of the porous graphene on the copper substrate is first etched, which helps to remove the influence of the graphene on the back side of the copper substrate on the subsequent film making. Since it is necessary to etch the back surface of the copper foil first, the graphene attached to the back side is loosened, which is convenient for subsequent rinsing and removal with deionized water, a shorter back etching time is selected; if the etching time is too long, the sample will lose the support of the copper foil substrate and cannot be rinsed with deionized water. Since the etching solution may contact the Nafion membrane during the etching process, the use of traditional ammonium persulfate solution may corrode the Nafion membrane synchronously, so a high-concentration FeCl3 solution is selected in the present invention. After the copper foil is etched, the ion residues on the surface of the porous graphene are removed by repeated cleaning with deionized water and a high-concentration hydrochloric acid solution.

[0022] Furthermore, multiple spin coatings are performed on the porous graphene surface, which can effectively reduce the interface stress between the first spin-coated film and the graphene, and reduce the possibility of graphene damage due to local stress concentration in the subsequent preparation process.

[0023] Furthermore, the spin coating and hot pressing process is repeated on the other side of the porous graphene to ensure that both sides of the porous graphene can be well fitted with Nafion and have sufficient mechanical support.

[0024] Furthermore, the composite membrane prepared by immersion in high-concentration acid is beneficial to ion exchange in Nafion, so that there are sufficient protons in its microstructure, which helps to improve the proton conductivity in subsequent battery applications.

[0025] In summary, the present invention proposes a novel proton exchange membrane of Nafion / large-area single-layer nanoporous graphene / Nafion composite structure, which ensures its excellent proton conductivity and methanol selectivity; the composite membrane has stable interface bonding at the interface and has good mechanical properties as a whole.

[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings to be used in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1The present invention is a flow chart of the preparation of the proton exchange membrane involved in the present invention: a) is graphene on a copper substrate prepared by CVD; b) is plasma treatment; c) is Nafion spin coating; d) is secondary hot pressing; e) is copper etching; f) is porous graphene on the Nafion film; g) is spin coating on the graphene surface again; h) is hot pressing compounding; Figure 2 Comparison diagram of the composite film interface before and after the spin coating process: a) is the composite film interface without the spin coating process; b) is the composite film interface after the spin coating process; Figure 3 Characterization results of graphene and composite membranes prepared by CVD: a) Scanning electron microscope (SEM) image of graphene on SiO2 / Si substrate; b) Raman spectrum of graphene on copper substrate; c) SEM image of graphene on N212 substrate; d) Cross-sectional SEM image of N212 / graphene / N212 membrane; e) Contact angle measurement of N212 membrane; f) Contact angle measurement of N212 membrane after graphene transfer; g) Photo of synthesized N212 / graphene / N212 membrane; h) Photo of synthesized MEA; Figure 4 To characterize nanoporous graphene: a) is a photo of the plasma treatment process; b) is the Raman spectrum of graphene obtained with different pore-forming times; Figure 5 To test the performance of N212 / nanoporous graphene / N212 series membranes: a) proton conductivity test; b) methanol permeability test; c) selectivity performance results; Figure 6 The performance test results of direct methanol fuel cell (DMFC) of N212 / nanoporous graphene / N212 series membranes. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.

[0031] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0032] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.

[0033] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.

[0034] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" represents that all real numbers between "6-22" are listed in this document, and "6-22" is just an abbreviation of these numerical combinations.

[0035] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.

[0036] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0037] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.

[0038] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.

[0039] The present invention provides a proton exchange membrane based on a large-area single-layer nanoporous graphene and Nafion composite and a preparation method thereof. On the basis of the prior art, a large-area single-layer nanoporous graphene is introduced, which can effectively utilize the atomic-level selectivity of graphene, and improve its methanol blocking ability while basically maintaining the proton conduction ability of the Nafion membrane. With respect to the interface treatment of the composite structure, the present invention optimizes multiple spin coatings on both sides of the graphene, ensuring good fit between the two-phase interface of Nafion and graphene, so that protons can be stably and efficiently transmitted.

[0040] See also Figure 1 The present invention provides a method for preparing a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite, comprising the following steps: S1, performing plasma etching on the porous graphene sample to obtain a porous graphene / copper foil sample; Graphene on a copper substrate grown by chemical vapor deposition (CVD); After gently flattening the copper foil with a clean glass plate, fix the four corners with the graphene side facing up with tape to make the sample adhere to the clean glass plate; put the glass plate into the chamber of the plasma cleaner, evacuate for 5 to 30 minutes, adjust the argon pressure in the chamber to 1.5 to 1.7 mbar and balance for 5 to 30 minutes, set the plasma power to 15 to 25 W, and the argon plasma etching time to 5 to 10 seconds; after breaking the vacuum in the chamber, place a homemade Faraday copper mesh on the graphene sample, evacuate for 5 to 30 minutes, adjust the oxygen pressure in the chamber to 0.25 to 0.4 mbar and balance for 5 to 30 minutes, set the plasma power to 5 to 10 W, and adjust the oxygen etching time according to the target screening aperture.

[0041] The Faraday copper grid is made of 5-20 mesh copper grids connected together to protect the graphene sample on the copper foil from the four sides and the top, and appropriately weaken the plasma intensity inside the copper grid.

[0042] S2, spin coating a layer of Nafion latex on the graphene surface of the porous graphene / copper foil sample, repeating the above steps to form a Nafion support layer of relatively thick thickness on the surface of the porous graphene; Add a few drops of Nafion latex on the surface of the porous graphene on the copper substrate to completely cover the graphene surface, spin coat at 400-500 rpm for 10-30 seconds, and then spin coat at 500-1500 rpm for 30-60 seconds; repeat the spin coating several times.

[0043] S3, drying and curing the spin-coated porous graphene / copper foil sample on a hot stage, and hot-pressing a Nafion film onto the spin-coated side of the graphene sample to obtain a Nafion / porous graphene / copper foil sample; Place the porous graphene / copper foil sample with the spin-coated side facing up, set the hot stage temperature to 115~140℃, and the curing time to 10~30 minutes.

[0044] The thickness of the Nafion film used is 10~183μm, the pressure used for hot pressing is 2.5~4.0 MPa, the hot pressing time is 2~10 minutes, and the hot pressing temperature is 125~140℃.

[0045] S4, etching the hot-pressed Nafion / porous graphene / copper foil sample in an etching solution to remove the material attached to the back of the copper foil, then rinsing the back of the membrane, placing it in a clean etching solution to etch the remaining copper foil, and after the etching is completed, washing the Nafion / porous graphene sample to remove the etching solution residue, and drying the Nafion / porous graphene sample to obtain a Nafion / graphene sample; The etching solution is 0.1~0.5M FeCl3 solution. During etching, the copper foil faces downward so that the sample floats on the surface of the etching solution. The etching time is 5~10 minutes. Deionized water (DIW) is used to rinse the surface of the copper foil to remove surface impurities, and then the remaining copper foil is etched with a clean 0.1~0.5M FeCl3 solution. After etching for 1~3 hours, the transparent Nafion / porous graphene membrane is washed in deionized water for 5~30 minutes, 5%~15% HCl solution for 5~30 minutes, and finally washed again with deionized water for 5~30 minutes. The Nafion / porous graphene sample is placed with the graphene side facing upward on a dust-free paper and dried overnight in the air.

[0046] S5, continuing to spin-coat a layer of Nafion latex on the graphene surface of the dried Nafion / porous graphene sample to enhance the interfacial adhesion; Add Nafion latex to the graphene surface of the Nafion / porous graphene sample so that the latex completely covers the sample, spin-coat at 400-500 rpm for 10-30 seconds, and then spin-coat at 500-1500 rpm for 30-60 seconds; repeat the spin-coating several times.

[0047] S6, drying and curing the spin-coated Nafion / porous graphene sample on a hot stage, and then hot-pressing and compounding it with another Nafion film to obtain a Nafion / porous graphene / Nafion sample; The spin-coated surface of the Nafion / porous graphene sample was placed facing upward and heated on a hot plate at 115-140°C for curing for 10-30 minutes. Then, a Nafion film with a thickness of 12-183 μm was selected, and the spin-coated surface of the Nafion / porous graphene sample was placed facing upward and hot-pressed with the Nafion film at a pressure of 2.5-4.0 MPa, a hot-pressing time of 10 minutes, and a hot-pressing temperature of 125-140°C to obtain a Nafion / porous graphene / Nafion sample.

[0048] S7. Soak the prepared Nafion / graphene / Nafion sample in an acid solution and then dry it to obtain a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite for use in the assembly of a membrane electrode assembly (MEA).

[0049] The acid solution is 5% to 15% HCl solution, the immersion time is 10 to 40 hours, and the drying condition is to place it on dust-free paper and dry it in the air overnight.

[0050] The proton exchange membrane based on the single-layer large-area nanoporous graphene / Nafion composite structure prepared by the method of the present invention can achieve an open circuit voltage of more than 0.5V and a power consumption of 130mW cm-2 at a test condition of more than 60°C after assembling a direct methanol fuel cell. -2 The above maximum power density is better than that of commercial Nafion membranes with the same thickness.

[0051] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0052] Example 1 S1. Gently flatten the copper-based graphene obtained by CVD with two clean glass plates, with the graphene side facing up, and fix it on a clean glass plate with four corners taped with tape, and move it into the plasma cleaning machine cavity. After the plasma cleaning chamber is evacuated for 5 minutes, the argon pressure in the chamber is adjusted to 1.5 mbar and then balanced for 5 minutes. The plasma power is set to 15 W, and the argon plasma etching time is 5 seconds. After the vacuum in the cavity is broken, a homemade Faraday copper mesh is placed on the graphene sample. After evacuation for 5 minutes, the oxygen pressure in the chamber is adjusted to 0.25 mbar and then balanced for 5 minutes. The plasma power is set to 5 W, and the oxygen etching time is 10 seconds; S2, adding a few drops of Nafion latex on the copper substrate graphene surface after plasma etching so that it can completely cover the graphene surface, and then spin coating at 400 rpm for 10 seconds, and then spin coating at 500 rpm for 30 seconds; S3, repeating the above spin coating step once to form a thicker Nafion support layer; S4, place the spin-coated sample with the spin-coated surface facing up and cure it on a hot plate at 115°C for 30 minutes; S5. After curing, a piece of Gore M778.12 film was hot pressed on the spin-coated surface of the sample at a pressure of 2.5 MPa, a temperature of 125 °C, and a duration of 2 minutes. S6, the copper foil side of the hot pressed sample is floated in a 0.1M FeCl3 solution and etched for 10 minutes to etch the material attached to the back of the copper foil; S7. After etching is completed, the copper foil surface is rinsed with deionized water (DIW), and then placed on another clean 0.1M FeCl3 solution surface to complete the copper foil etching; S8. After 3 hours of etching, the sample is transparent. The sample is washed with deionized water for 5 minutes, then with 5% HCl solution for 5 minutes, and finally with deionized water for 5 minutes; S9, the sample was dried overnight in air with the graphene side facing up; S10, then, drop Nafion latex on the graphene surface of the sample to completely cover the sample, and spin-coat it on the membrane, and complete the spin coating with the same spin coating parameters as in step S2; repeat the spin coating twice; S11, place the sample with the spin-coated surface facing up on a hot plate at 115°C and dry for 30 minutes; S12, with the spin-coated surface of the dried sample facing upward, hot-press it with another Gore M778.12 film at a pressure of 2.5 MPa and a temperature of 125°C for 2 minutes; S13, soaking the hot pressed sample in 5% HCl solution for 40 hours and then drying in air; S14. Mix the sample with 2.0 mg cm -2 Platinum black loading (cathode) / 4.0 mg cm -2 The gas diffusion electrode with PtRu loading (anode) was hot pressed with the sample at a pressure of 3.0 MPa and a temperature of 135°C for 3 minutes to complete the membrane electrode preparation.

[0053] Example 2 S1. Gently flatten the copper-based graphene obtained by CVD with two clean glass plates, with the graphene facing up, and fix it on the clean glass plate with four corners taped with tape, and move it into the plasma cleaning machine cavity. After the plasma cleaning chamber is evacuated for 30 minutes, the argon gas pressure in the chamber is adjusted to 1.7 mbar and then balanced for 30 minutes. The plasma power is set to 25 W, and the argon plasma etching time is 10 seconds. After the vacuum of the cavity is broken, a homemade Faraday copper mesh is placed on the graphene sample. After evacuation for 30 minutes, the oxygen pressure in the chamber is adjusted to 0.4 mbar and then balanced for 30 minutes. The plasma power is set to 10 W, and the oxygen etching time is 10 seconds; S2, adding a few drops of D520 latex on the copper substrate graphene surface after plasma etching so that it can completely cover the graphene surface, and then spin coating at 500 rpm for 30 seconds, and then spin coating at 1500 rpm for 60 seconds; S3, repeating the above spin coating step once to form a thicker Nafion support layer; S4, place the spin-coated sample with the spin-coated surface facing up and cure it on a hot plate at 140°C for 10 minutes; S5. After curing, a piece of N117 film is hot pressed on the spin-coated surface of the sample at a pressure of 4.0 MPa, a temperature of 140 °C, and a duration of 10 minutes; S6, the copper foil side of the hot pressed sample is floated in a 0.5M FeCl3 solution and etched for 5 minutes to etch the material attached to the back of the copper foil; S7. After etching is completed, the copper foil surface is rinsed with deionized water (DIW), and then placed on another clean 0.5M FeCl3 solution surface to complete the copper foil etching; S8. After 1 hour of etching, the sample is transparent. The sample is washed with deionized water for 30 minutes, then with 15% HCl solution for 30 minutes, and finally with deionized water for another 30 minutes; S9, the sample was dried overnight in air with the graphene side facing up; S10, then, add D520 latex to the graphene surface of the sample to completely cover the sample, and spin-coat it on the film, and complete the spin coating with the same spin coating parameters as in S2; repeat the spin coating once; S11, place the sample with the spin-coated surface facing up on a hot plate at 140°C and dry for 10 minutes; S12, with the spin-coated surface of the dried sample facing upward, hot-press it with another N117 film at a pressure of 4.0 MPa and a temperature of 140°C for 10 minutes; S13, soaking the hot pressed sample in 15% HCl solution for 10 hours and then drying in air; S14. Mix the sample with 2.0 mg cm -2 Platinum black loading (cathode) / 4.0 mg cm -2 The gas diffusion electrode with PtRu loading (anode) was hot pressed with the sample at a pressure of 3.0 MPa and a temperature of 135°C for 3 minutes to complete the membrane electrode preparation.

[0054] Example 3 S1. Gently flatten the copper-based graphene obtained by CVD with two clean glass plates, with the graphene side facing up, and fix it on a clean glass plate with four corners taped with tape, and move it into the plasma cleaning machine cavity. After the plasma cleaning chamber is evacuated for 10 minutes, the argon gas pressure in the chamber is adjusted to 1.6 mbar and then balanced for 5 minutes. The plasma power is set to 20 W, and the argon plasma etching time is 6 seconds. After the vacuum is broken in the cavity, a homemade Faraday copper mesh is placed on the graphene sample. After evacuation for 10 minutes, the oxygen pressure in the chamber is adjusted to 0.3 mbar and then balanced for 5 minutes. The plasma power is set to 7 W, and the oxygen etching time is 20 seconds; S2, adding a few drops of D520 latex on the copper substrate graphene surface after plasma etching so that it can completely cover the graphene surface, and then spin coating at 450 rpm for 15 seconds, and then spin coating at 1000 rpm for 45 seconds; S3, repeating the above spin coating step once to form a thicker Nafion support layer; S4, place the spin-coated sample with the spin-coated surface facing up and cure it on a hot plate at 120°C for 20 minutes; S5. After curing, a piece of N212 film was hot-pressed on the spin-coated surface of the sample at a pressure of 3.0 MPa, a temperature of 135°C, and a duration of 3 minutes; S6, the copper foil side of the hot pressed sample is floated in a 0.3M FeCl3 solution and etched for 7 minutes to etch the material attached to the back of the copper foil; S7. After etching is completed, the copper foil surface is rinsed with deionized water (DIW), and then placed on another clean 0.3M FeCl3 solution surface to complete the copper foil etching; S8. After 2 hours of etching, the sample is transparent. The sample is washed with deionized water for 10 minutes, then with 10% HCl solution for 10 minutes, and finally with deionized water for another 10 minutes; S9, the sample was dried overnight in air with the graphene side facing up; S10, then, add D520 latex to the graphene surface of the sample to completely cover the sample, and spin-coat it on the film, and complete the spin coating with the same spin coating parameters as in S2; repeat the spin coating twice; S11, place the sample with the spin-coated surface facing up on a hot plate at 120°C and dry for 20 minutes; S12, with the spin-coated surface of the dried sample facing upward, hot-press it with another N212 film at a pressure of 3.0 MPa and a temperature of 135°C for 10 minutes; S13, soaking the hot pressed sample in 10% HCl solution for 24 hours and then drying in air; S14. Mix the sample with 2.0 mg cm -2 Platinum black loading (cathode) / 4.0 mg cm -2 The gas diffusion electrode with PtRu loading (anode) was hot pressed with the sample at a pressure of 3.0 MPa and a temperature of 135°C for 3 minutes to complete the membrane electrode preparation.

[0055] Example 4 S1. Gently flatten the copper-based graphene obtained by CVD with two clean glass plates, with the graphene side facing up, and fix it on a clean glass plate with four corners taped with tape, and move it into the plasma cleaning machine cavity. After the plasma cleaning agent cavity is evacuated for 10 minutes, the argon gas pressure in the cavity is adjusted to 1.5 mbar and then balanced for 10 minutes. The plasma power is set to 20 W, and the argon plasma etching time is 6 seconds. After the cavity is vacuumed, a homemade Faraday copper mesh is placed on the graphene sample. After evacuation for 20 minutes, the oxygen pressure in the cavity is adjusted to 0.35 mbar and then balanced for 5 minutes. The plasma power is set to 7 W, and the oxygen etching time is 10 seconds; S2, adding a few drops of D520 latex on the copper substrate graphene surface after plasma etching so that it can completely cover the graphene surface, and then spin coating at 450 rpm for 20 seconds, and then spin coating at 1500 rpm for 45 seconds; S3, repeating the above spin coating step once to form a thicker Nafion support layer; S4, place the spin-coated sample with the spin-coated surface facing up and cure it on a hot plate at 130°C for 20 minutes; S5. After curing, a piece of N212 film was hot pressed on the spin-coated surface of the sample at a pressure of 3.0 MPa, a temperature of 135°C, and a duration of 5 minutes; S6, the copper foil side of the hot pressed sample is floated in a 0.3M FeCl3 solution and etched for 7 minutes to etch the material attached to the back of the copper foil; S7. After etching is completed, the copper foil surface is rinsed with deionized water (DIW), and then placed on another clean 0.3M FeCl3 solution surface to complete the copper foil etching; S8. After 2 hours of etching, the sample is transparent. The sample is washed with deionized water for 20 minutes, then with 10% HCl solution for 20 minutes, and finally with deionized water for 20 minutes; S9, the sample was dried overnight in air with the graphene side facing up; S10, then, add D520 latex to the graphene surface of the sample to completely cover the sample, and spin-coat it on the film, and complete the spin coating with the same spin coating parameters as in S2; repeat the spin coating twice; S11, place the sample with the spin-coated surface facing up on a hot plate at 130°C and dry for 20 minutes; S12, with the spin-coated surface of the dried sample facing upward, hot-press it with another N212 film at a pressure of 3.0 MPa and a temperature of 135°C for 10 minutes; S13, immersing the hot pressed sample in a 10% HCl solution for 30 hours and then drying in air; S14. Mix the sample with 2.0 mg cm-2 Platinum black loading (cathode) / 4.0 mg cm -2 The gas diffusion electrode with PtRu loading (anode) was hot pressed with the sample at a pressure of 3.0 MPa and a temperature of 135°C for 3 minutes to complete the membrane electrode preparation.

[0056] Through scanning electron microscopy characterization of the cross-section, it can be seen that after the introduction of the double-sided spin coating process, close fitting between graphene and the Nafion film interface can be effectively achieved.

[0057] Through preliminary experimental characterization, such as Figure 3 (a) and Figure 3 As shown in (b), the CVD graphene used in the experiment is a large-area continuous single layer, and Raman characterization shows basically no obvious material defects, thus avoiding the influence of the material itself on subsequent experimental results. Figure 3 (c) The interface between Nafion and graphene on Nafion can be clearly observed. Figure 3 (e) and Figure 3 (f) The contact angle test results prove the successful large-area transfer of graphene on the Nafion film. Figure 3 (g) and Figure 3 (h) shows the actual picture of the prepared film and MEA.

[0058] Figure 4 The process and result characterization of plasma pore formation of graphene on copper foil are demonstrated. Raman spectroscopy characterization, such as Figure 4 As shown in (b), adjusting the oxygen plasma treatment time can effectively control the defects on the graphene surface and achieve different pore-forming effects.

[0059] Figure 5 The conductivity of the proton exchange membrane (a) obtained by four-electrode scanning voltammetry in a hydrochloric acid solution with a pH of 1, the methanol permeation obtained by installing the proton exchange membrane between a 0.5M methanol solution and a deionized water chamber (b), and the selectivity of the proton exchange membrane calculated based on the proton conductivity and methanol permeability (c) are shown. It can be seen that oxygen plasma pore formation can effectively improve the conductivity performance of the proton exchange membrane. Figure 5 As shown in a; compared with the commercial Nafion membrane, the methanol permeation is significantly reduced after the introduction of nanoporous graphene, as shown in Figure 5 As shown in b; oxygen treatment time has little effect on methanol permeability, but mainly affects proton conductivity, thus dominating the change of proton exchange membrane selectivity, such as Figure 5 As shown in c.

[0060] After preparing MEA by combining graphene films with different pore-forming times with Nafion films, the performance of direct methanol fuel cells was tested. The methanol fuel was a 5.0M methanol aqueous solution, and the test temperature was 60°C. After the MEA battery was assembled, it was activated with a constant current for 5 hours and the battery performance was tested. The test results are as follows: Figure 5 The sample treated with oxygen plasma for 10 s showed the best battery performance, with an open circuit voltage of 0.532 V and a maximum power density of 134.56 mW cm -2 .

[0061] In summary, the proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite and its preparation method proposed in the present invention can effectively and simultaneously improve the methanol selectivity and proton conductivity of the proton exchange membrane, and achieve a simultaneous improvement in the battery open circuit voltage and power density in direct methanol fuel cell applications compared to existing commercial proton exchange membranes of the same thickness.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite, characterized in that: The following steps are involved: S1, performing plasma etching on the graphene sample to obtain a porous graphene / copper foil sample; S2, spin coating a layer of Nafion latex on the graphene surface of the porous graphene / copper foil sample prepared in step S1, and repeating the process multiple times; S3, drying and curing the porous graphene / copper foil sample after spin coating in step S2 on a hot stage, hot pressing a Nafion film on the spin-coated side of the graphene sample to obtain a Nafion / porous graphene / copper foil sample; S4, etching the Nafion / porous graphene / copper foil sample after hot pressing in step S3 in an etching solution to remove the material attached to the back side of the copper foil, then rinsing the back side of the copper foil, placing the sample back in a clean etching solution to etch the remaining copper foil, and washing and drying after the etching is completed to obtain a Nafion / graphene sample; S5, continuing to spin-coat a layer of Nafion latex on the graphene surface of the Nafion / porous graphene sample dried in step S4; S6, drying and curing the Nafion / graphene sample after spin coating in step S5 on a hot stage, and then hot-pressing and compounding with another Nafion film to obtain a Nafion / porous graphene / Nafion sample; S7, soaking the Nafion / porous graphene / Nafion sample prepared in step S6 in an acid solution and then drying it to obtain a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite.

2. The method for preparing a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite according to claim 1, characterized in that: In step S1, the porous graphene on the copper substrate obtained by chemical vapor deposition growth is flattened with a glass plate, with the porous graphene facing upward, so that the sample is attached to the glass plate; the glass plate is placed in a cavity of a plasma cleaning agent, and vacuumed for 5 to 30 minutes, and the argon gas pressure in the cavity is adjusted to 1.5 to 1.7 mbar and then balanced for 5 to 30 minutes, the plasma power is set to 15 to 25 W, and the argon plasma etching time is 5 to 10 seconds; after the cavity is broken by vacuum, a Faraday copper mesh is placed on the porous graphene sample, and after vacuuming for 5 to 30 minutes, the oxygen gas pressure in the cavity is adjusted to 0.25 to 0.4 mbar and then balanced for 5 to 30 minutes, and the plasma power is set to 5 to 10 W.

3. The method for preparing a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite according to claim 1, characterized in that: In step S2, spin coating a layer of Nafion latex is specifically as follows: Spin coat at 400-500 rpm for 10-30 seconds, and then at 500-1500 rpm for 30-60 seconds to complete a layer of Nafion latex.

4. The method for preparing a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite according to claim 1, characterized in that: In step S3, the drying and curing temperature is 115-140° C. and the time is 10-30 min.

5. The method for preparing a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite according to claim 4, characterized in that: The thickness of the Nafion film is 12~183μm, the pressure used for hot pressing is 2.5~4.0 MPa, the hot pressing time is 2~10min, and the hot pressing temperature is 125~140℃.

6. The method for preparing a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite according to claim 1, characterized in that: In step S4, the etching time is 5 to 10 minutes; the back of the copper foil is rinsed with deionized water, and then the remaining copper foil is etched with a 0.1 to 0.5 M FeCl3 solution; after etching for 1 to 3 hours, the transparent N212 / porous graphene membrane is washed in deionized water for 5 to 30 minutes, washed with a 5% to 15% HCl solution for 5 to 30 minutes, and finally washed again with deionized water for 5 to 30 minutes.

7. The method for preparing a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite according to claim 1, characterized in that: In step S5, a layer of Nafion latex is further spin-coated as follows: Spin at 400-500 rpm for 10-30 s, then at 500-1500 rpm for 30-60 s.

8. The method for preparing a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite according to claim 1, characterized in that: In step S6, the drying and curing temperature is 115-140°C, the time is 10-30 min, and then a Nafion film with a thickness of 12-183 μm is selected, and the spin-coated surface of the Nafion / porous graphene / copper foil sample is hot-pressed with the Nafion film facing upward, the hot-pressing pressure is 2.5-4.0 MPa, the hot-pressing time is 2-10 min, and the hot-pressing temperature is 125-140°C.

9. The method for preparing a proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite according to claim 1, characterized in that: In step S7, the acid solution is a 5% to 15% HCl solution, and the soaking time is 10 to 40 hours.

10. A proton exchange membrane based on a large-area single-layer nanoporous graphene Nafion composite prepared according to the method of any one of claims 1 to 9, characterized in that: Under the test conditions of 60~90℃, the open circuit voltage can reach more than 0.5V and the power consumption can reach 130 mW cm -2 Maximum power density above .

Citation Information

Patent Citations

  • Sandwich structure heat dissipation film based on graphene, semiconductor device and preparation method thereof

    CN112490204A

  • Preparation method of graphene composite membrane and application of graphene composite membrane in liquid fuel cell

    CN116914174A

  • Hybrid membranes for energy-efficient carbon capture

    EP3593893A1

  • Polymer actuators containing graphene and method for preparing the same

    KR1020110062218A

  • Carbon-based oxygen reduction catalyst, preparation method therefor and use thereof

    WO2018121365A1